PEMANFAATAN AIR KELAPA MUDA SEBAGAI MEDIA ALTERNATIF MAC CONCEY UNTUK PERTUMBUHAN Escherichia coli DAN Salmonella typhi - Sari Artauli Lumban Toruan; Thomas Tandi Manu; Paulina Rosa Evriarti (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2023)
The growth of microorganisms requires media as a material consisting of a mixture of nutrients. used to grow microbes This study is laboratory experiment that aims to determine the protein composition on an old coconut water which is used as an alternative Mac Conkey Agar that can be used for growth of Escherichia coli and Salmonella typhi to characterized by non fermenter lactose and fermenter lactose colony. Research method is experimental test using inoculated on alternative media and Mac Conkey Agar as a control. Old coconut water media composition composed resemble for Mac Conkey Agar and media control that the order for Mac Conkey Agar. The bacterium is Escherichia coli and Salmonella typhi as test bacteria fermenter non fermenter lactose and lactose. Analysis of data using T test results showed an old coconut water alternative media can foster better Escherichia coli when compared to Salmonella typhi, because there is no difference in the number and diameter of colonies significantly to media controls. In the alternative media do not growth old coconut water Salmonella typhi the same controls. Based on the results of the research can be concluded that Escherichia coli and Salmonella typhi can grow on alternative media of Old Coconut Water.